Sex-specific differences in the salivary microbiome of caries-active children. Issue 1 (1st January 2019) - Ortiz, Stephanie; Herrman, Elisa; Lyashenko, Claudia; Purcell, Anne; Raslan, Kareem; Khor, Brandon; Snow, Michael; Forsyth, Anna; Choi, Dongseok; Maier, Tom; Machida, Curtis A.
ABSTRACT: Background and Objectives : Dental caries is a chronic disease affecting young children and has multi-factorial risk factors. The purpose of this work was to identify sex-specific differences in the salivary microbiota within caries-active children. Design : Saliva specimens were collected from 85 children (boys: 41; girls: 44) between the ages of 2-12 years. Salivary microbial DNA was subjected to PCR amplification using V3-V4 16S rDNA-specific primers and next-generation sequencing. Results : Significant sex differences in salivary microbiota were found between caries-active boys versus caries-active girls. Neisseria flavescens, Rothia aeria, and Haemophilus pittmaniae were found at significantly higher levels in caries-active boys. In contrast, Lactococcus lactis, Selenomonas species HOT 126, Actinobaculum species HOT 183, Veillonella parvula, and Alloprevotella species HOT 473 were found at significantly higher levels in caries-active girls. Conclusion : We have found the acid-generating, cariogenic Lactococcus lactis to be much more abundant in caries-active girls than caries-active boys, indicating that this microorganism may play a more significant role in shaping the cariogenic microbiome in girls. In addition, in caries-active girls, Alloprevotella species HOT 473 was the only species that exhibited both significant sex differences (4.4-fold difference; p=0.0003) as well as high abundance in numbers (1.85% of the total microbial population).